A combined assessment of air and noise pollution on the High Line, New York City. (January 2016) - King, E.A.; Bourdeau, E.P.; Zheng, X.Y.K.; Pilla, F.
Highlights: This paper offers a combined assessment of noise and air pollution in an urban environment. Air and noise pollution measurements were taken along an elevated public park to investigate potential reductions in exposure. Results are expressed through a novel combined air–noise pollution index. The average reduction in air and noise pollution along the High Line compared to the footpath below is 37%. Abstract: The High Line is an elevated public park in New York City, transformed from an unused freight rail line. Pedestrians walking through Manhattan's West Side can walk either on the High Line or on a footpath below. Using Manhattan as a laboratory, this paper offers a combined assessment of noise and particulate matter pollution for its pedestrians. Noise and PM2.5 levels were recorded simultaneously for two cases (i) pedestrians walking on a footpath alongside road traffic and (ii) pedestrians walking on the elevated High Line. Testing took places over three days in autumn 2014. Results were analysed to investigate if pedestrians using the High Line would have a lower pollution exposure to those using the footpath below. Results showed statistically significant differences between the upper and lower levels in exposure to both pollution types. In order to quantify the overall impact, results are expressed through a combined air–noise pollution index. This index indicates that the average reduction in PM2.5 and noise pollution along the High Line compared to the footpath below is approximately 37%.